Little ice age advance and retreat sediment budgets for an outlet glacier in western Norway - Burki, V.; Hansen, L.; Fredin, O.; Andersen, T.A.; Beylich, A.A; Jaboyedoff, M.; Larsen, E.; Tönnesen, J.-F. (Boreas, 2010)
Bødalsbreen is an outlet glacier of the Jostedalsbreen Ice Field in western Norway. Nine moraine ridges formed during and after the maximum extent of the Little Ice Age (LIA). The stratigraphy of proglacial sediments in the Bødalen basin inside the LIA moraines is examined, and corresponding sediment volumes are calculated based on georadar surveys and seismic profiling. The total erosion rates (etot) by the glacier are determined for the periods AD 1650?1930 and AD 1930?2005 as 0.8 ± 0.4 mm/yr and 0.7 ± 0.3 mm/yr, respectively. These rates are based on the total amount of sediment delivered to the glacier margin. The values are almost one order of magnitude higher than total erosion rates previously calculated for Norwegian glaciers. This is explained by the large amount of pre-existing sediment that was recycled by Bødalsbreen. Thus, the total erosion rate must be considered as a composite of eroded bedrock and of removed pre-existing sediments. The total erosion rate is likely to vary with time owing to a decreasing volume of easily erodible, unconsolidated sediment and till under the glacier. A slight increase in the subglacial bedrock erosion is expected owing to the gradually increasing bedrock surface area exposed to subglacial erosion.